Original paper Evaluation of the nailfold skin capillaroscopic modifications of psoriatic patients and levels of the transforming growth factor α and vascular endothelial growth factor: an initiative paper - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia; Syguła, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Psoriasis occurs in 1-5% of population and admissions to hospitals include 6-8% of patients in the dermatological wards. Angiogenesis plays a role in pathogenesis of many skin disorders and it is one of basic phenomena observed in psoriasis. Aim : The aim of this study was to compare capillaroscopic images and neovascularisation factors in the patients diagnosed with psoriasis as well as to assess progress in psoriasis treatment in this group of patients. Results : The preliminary analysis showed existence of a statistically significant correlation between tumour growth factor α (TGF- α) and vascular endothelial growth factor (VEGF) levels in the patients’ sera and the capillaroscopic image of these patients. Additionally, a correlation was observed between PASI results, tested neovascularisation factors and capillaroscopic images. The obtained results suggest a possibility to use capillaroscopy and diagnosis of neovascularisation factors to diagnose and assess the progress of psoriasis treatment. Conclusions : The study had a preliminary character and it is still continued. Key words: psoriasis vulgaris, capillaroscopy, angiogenesis.